On K‐stability of finite covers. (28th June 2016) - Dervan, Ruadhaí
Abstract : We show that certain Galois covers of K‐semistable Fano varieties are K‐stable. We use this to give some new examples of Fano manifolds admitting Kähler–Einstein metrics, including hypersurfaces, double solids and threefolds.